Whole-Body MRI for Inflammatory Arthritis and Other Multifocal Rheumatoid Diseases - Weckbach, Sabine (Seminars in Musculoskeletal Radiology, 2012)
Whole-body MRI (WBMRI) is an excellent tool for the imaging of rheumatologic diseases with a multifocal and systemic character. These include the different forms of spondyloarthritis, chronic recurrent multifocal osteomyelitis (CRMO), and inflammatory muscle diseases along with diseases such as systemic lupus and systemic sclerosis that show organ involvement. Although it is not recommended as a first-line investigation in every patient, it may add important information in difficult cases.Currently WBMRI for inflammatory arthritis is mainly used in imaging the seronegative spondyloarthropathies. The technique visualizes most of the involved joints and soft tissue structures with both (early) active and chronic inflammatory changes in one examination. Different patterns of joint involvement can be recognized, with both the acute features of the disease and the longer term sequelae being shown. The technique also allows therapeutic response to be assessed.In CRMO, WBMRI is able to detect asymptomatic and radiographically occult multifocal lesions that typically show a symmetrical distribution predominating in the lower extremity.In inflammatory muscle diseases, WBMRI is able to provide important information for biochemical and genetic differential diagnosis because there is growing knowledge of the correlation between typical patterns of disease and defined clinical entities. In addition, it helps in biopsy localization and is very well suited for assessing disease activity.WBMRI is particularly useful for studying internal organ involvement, especially the brain, heart, and lungs in connective tissue diseases such as systemic lupus erythematosus in one whole-body exam.
Keywords: whole-body MRI; inflammatory arthritis; ankylosing spondylitis; CRMO; inflammatory myopathy; MR protocol; multifocal disease